PERAN CLEAR RIVERS DALAM PENANGANAN SAMPAH DI KOTA AMBON PADA TAHUN 2022 - Wardani, Retno Trisna; ', Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Ambon City is one of the cities in Indonesia that has regulations related to waste management. The existence of these regulations does not make Ambon City a good city in handling its waste. This can be seen by the increasing trend in the amount of waste volume each year in Ambon City. Non-Governmental Organization as one of the actors that can have a strategic role and be able to realize a circular economy in handling waste in Indonesia. One of the Non-Governmental Organizations that has taken part in efforts to deal with waste on both land and water in Indonesia is Clear Rivers. More specifically, it can be seen in the Ambon Plastic-Free project. Ambon Plastic-Free is a prevention project in handling waste, especially plastic waste in Ambon City. The purpose of this research is to see the causes of waste pollution in Ambon City, to know the role of Clear Rivers as a Non-Governmental Organization in handling waste and to see the synergy between Clear Rivers and other actors in handling waste in Ambon City. This research is a qualitative research with data collection techniques in the form of interviews and literature studies. This research refers to the typology of strategies listed in Sikkink and Keck's theory. The results of this study show that the strategies used by Clear Rivers in this project include information politics which is reflected in education, Cleanups and awareness activities through social media, leverage politics which is seen in approaches to parties from the smallest scope that have the power to be able to mobilize the community, and accountability politics carried out by Clear Rivers to the Ambon City government regarding the transfer of responsibility for Litter Traps. Keywords: Non-Governmental Organization, Clear Rivers, Handling, Waste